Electronic structure of Pr2MnNiO6 from x-ray photoemission, absorption and density functional theory. (4th October 2018) - Balasubramanian, Padmanabhan; Joshi, Shalik Ram; Yadav, Ruchika; de Groot, Frank M F; Singh, Amit Kumar; Ray, Avijeet; Gupta, Mukul; Singh, Ankita; Maurya, Satyendra; Elizabeth, Suja; Varma, Shikha; Maitra, Tulika; et al.
Abstract: The electronic structure of double perovskite Pr2 MnNiO6 was studied using core x-ray photoelectron spectroscopy and x-ray absorption spectroscopy. The 2 p x-ray absorption spectra show that Mn and Ni are in 4+ and 2+ states respectively. Based on charge transfer multiplet analysis of the 2 p XPS spectra of both ions, we find charge transfer energies of 3.5 and 2.5 eV for Ni and Mn respectively. The ground state of Ni 2+ and Mn 4+ ions reveal a higher d electron count of 8.21 and 3.38 respectively as compared to the ionic values. The partial density of states clearly show a charge transfer character of the system for U − J 2 eV. The O 1 s edge absorption spectra reveal a band gap of 0.9 eV, which is close to the value estimated from analysis of Ni and Mn 2 p photoemission and absorption spectra. The combined analysis of nature of spectroscopic data and first principles calculations reveal that the material is a p − d type charge transfer insulator with an intermediate covalent character according to the Zannen–Sawatzy–Allen phase diagram.